Implementation of Analytical Hierarchy Process in Determining Customer Relationship Management Features in Regional Syariah Banks - Nurul Muslimah; Muhammad Saiful Hakim (Politeknik Siber Cerdika Internasional, 2025)
Background: Limited resources and the increasing complexity of service needs pose significant challenges for regional Islamic banks in prioritizing Customer Relationship Management (CRM) system features. PT Bank NTB Syariah faces fragmented customer data management, limited customer behavior analysis, and ongoing regulatory and security compliance demands, necessitating a structured decision-making approach. Objective: This study aims to determine CRM system feature priorities quantitatively and objectively using the Analytical Hierarchy Process (AHP) method. Method: The study employed AHP involving five internal expert panelists representing information technology, business, compliance, and service quality functions. Four evaluation criteria were established: (1) business performance improvement, (2) customer relationship management, (3) customer data and information management, and (4) compliance and security. Pairwise comparisons determined criteria and alternative priorities, with consistency ratios calculated to ensure reliability. Result: The AHP analysis revealed that customer data and information management received the highest weight among the evaluation criteria, highlighting the strategic importance of data in Islamic banking digital transformation. At the alternative level, the Customer 360° View feature obtained the highest priority weight (0.2586), followed by Omnichannel Interaction & Complaint Management (0.2307), and AI Chatbot & Digital Assistant (0.1080). All pairwise comparison matrices achieved a Consistency Ratio (CR) value of ≤ 0.10, confirming consistent and reliable judgments. Conclusion: This study provides a structured multi-criteria decision-making framework based on AHP for prioritizing CRM feature implementation in regional Islamic banks. The findings support measurable and strategic resource allocation while enhancing service quality and accelerating digital transformation efforts.